Inertial support from WPPs that include VSWTs – a review. Issue 7 (13th May 2019) - Wu, Yuan‐Kang; Hu, Yi‐Liang; Hsu, Wen‐Hua
Abstract : Maintaining the frequency within an allowable range is the necessity to ensure the stable operation of the grid. When a large‐scale frequency disturbance occurs in the grid, the synchronous generators (SGs) will temporarily release the kinetic energy to make the generation and demand balanced. This is well known as the inertial response of the SG. However, the traditional variable‐speed wind turbines (VSWTs) only generate a negligible inertial response when a frequency disturbance happens. The traditional VSWT is designed to maximise the wind energy injected into the grid. Thus, when a frequency disturbance is detected in the grid, the traditional VSWT cannot change the active power output to support the grid. To solve this problem, the concepts of the inertial control and inertial support capability for VSWT were proposed. The inertial control measures the frequency of the grid and adjusts the active power output of VSWT. Thus, during the frequency disturbance, the VSWT has the inertial support capability. The purpose of this study is to provide a comprehensive review of the inertial control for the wind power plant (WPP) consisting of VSWTs. With the inertial control, the integration of the WPPs can enhance the frequency stability of the grid.